2022
DOI: 10.33200/ijcer.919958
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of PISA and PIAAC Participants’ Reading Habits and Strategies in Terms of Reading Achievement

Abstract: This study aimed to compare reading strategies and habits regarding reading achievement of selected age-group participants from the Programme for International Student Assessment (PISA) 2009 and the International Assessment of Adult Competencies (PIAAC) 2015 within Turkey. A cohort design was utilized because it was assumed that reading literacy from PISA and PIAAC were comparable, as well as that participants from PISA 2009 would be in the age range of participants at the time of PIAAC in 2015. The participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…When compared with individual scores, the number of female students who scored above the class average was 10 people (32.26%) while the number of male students who scored above the class average was only 2 people (6.45%). This finding is in line with PIRLS in 2016, Bijou & Mariem (2018), Yalcin & Bayraktar (2021), girls are better on PISA rather than boys. Syamsuri & Bancong (2022) who stated female students have better ready literacy in PISA than male students do.…”
Section: Average Valuesupporting
confidence: 85%
See 1 more Smart Citation
“…When compared with individual scores, the number of female students who scored above the class average was 10 people (32.26%) while the number of male students who scored above the class average was only 2 people (6.45%). This finding is in line with PIRLS in 2016, Bijou & Mariem (2018), Yalcin & Bayraktar (2021), girls are better on PISA rather than boys. Syamsuri & Bancong (2022) who stated female students have better ready literacy in PISA than male students do.…”
Section: Average Valuesupporting
confidence: 85%
“…Bijou & Mariem (2018) also revealed that boys are no better than girls when it comes to reading. Investigated by Yalcin & Bayraktar (2021), girls are better on PISA rather than boys. Syamsuri & Bancong (2022) stated that due to good motivation and focus, female students have better reading skills than male students.…”
Section: Introductionmentioning
confidence: 97%